Effect of operating temperature on anaerobic digestion of the Brazilian waterweed Egeria densa and its microbial community. (October 2017) - Watanabe, Keiko; Koyama, Mitsuhiko; Ueda, Junko; Ban, Syuhei; Kurosawa, Norio; Toda, Tatsuki
Abstract: To develop an effective treatment for the globally invasive Brazilian waterweed Egeria densa, anaerobic digestion was observed at 37 °C, 55 °C, and 65 °C. The average methane production rate at 55 °C was 220 mL L −1 day −1, which was two-fold that at 37 °C and 65 °C. Volatile fatty acid accumulation was detected under thermophilic conditions; however, although there was methane production, the system did not shutdown. The microbial communities differed between mesophilic (37 °C) and thermophilic (55 °C and 65 °C) conditions. A bacterial community consisting of the phyla Bacteroidetes (43%), Firmicutes (37%), Proteobacteria (9%), Synergistetes (5%), Spirochaetes (1%), and unclassified bacteria (5%) were detected under mesophilic condition. In contrast, the phylum Firmicutes was dominant under thermophilic conditions. In the archaeal community, Methanosaeta concilii (40%), Methanolinea sp. (17%), and unclassified euryarchaeota (43%) were detected under mesophilic condition. Methanosarcina thermophila (87% at 55 °C, 54% at 65 °C) and Methanothermobacter thermautotrophicus (13% at 55 °C, 46% at 65 °C) were detected under thermophilic conditions. At both 37 °C and 55 °C, acetoclastic methanogenesis likely occurred because of the lower abundance of hydrogenotrophic methanogens. At 65 °C, the growth of the acetoclastic methanogen Methanosarcina thermophila was limited by the high temperature, therefore, acetate oxidation and hydrogenotrophic methanogenesis may have occurred. Highlights: For effective treatment of E. densa, temperature of anaerobic digestion was examined. The microbial diversity decreased and Firmicutes was dominant at 55 °C and 65 °C. Acetate oxidation and hydrogenotrophic methanogenesis may have been enhanced at 65 °C. 55 °C is a suitable, however, care must be taken to prevent the ammonia inhibition.